PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN IPAS KELAS IV UPTD SD INPRES LASIANA KOTA KUPANG - Yurni M.Nabut; Andriyani A. Dua Lehan; Netty E. A. Nawa; Sumardi W. Ndolu; Antonius Suban Hali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of wordwall learning media on students' creative thinking abilities in class IV science and science subjects at UPTD SD Inpres Lasiana, Kupang City. The research method used is quantitative with a pre-experimental design approach, one group pretest-posttest design type. The sample in this study were students of class IV B UPTD SD Inpres Lasiana, Kupang City. Data collection techniques in this research are observation, tests and documentation. Data analysis techniques in this research are normality test, homogeneity test and hypothesis test. The results of this research show that there is a significant influence in the use of wordwall learning media on the creative thinking abilities of class IV students in the UPTD UPTD science subject at SD Inpres Lasiana, Kupang City. This is proven by the results of hypothesis testing using a paired sample t-test with a significance level of 0.05, obtaining a sig (2-tailed) value of 0.000 < 0.05, which means H0 is rejected and Ha is accepted.